Seasonal changes in radiocesium and potassium concentrations in current-year shoots of saplings of three tree species in Fukushima, Japan. (November 2020) - Kenzo, Tanaka; Saito, Satoshi; Miura, Satoru; Kajimoto, Takuya; Kobayashi, Natsuko I.; Tanoi, Keitaro
Abstract: We studied seasonal changes in radiocesium ( 137 Cs) activity and potassium concentrations in current-year leaves and branches of Pinus densiflora (naturally regenerated saplings), Cryptomeria japonica (planted saplings) and Quercus serrata (planted saplings and coppice shoots) in Fukushima, Japan. We collected current-year shoots from 10 individuals of each species over two growing seasons at intervals of 1–4 months, between June 2016 and December 2017. For the deciduous species Q . serrata, we also collected dead leaves that remained attached to branches in December to investigate reabsorption of 137 Cs. All collected shoots were divided into leaves and branches, oven-dried, and ground; dry weights of each sample were recorded. 137 Cs activity concentrations were measured using a germanium semiconductor detector. Potassium concentrations were quantified using inductively coupled plasma optical emission spectrometry (ICP-OES). Increases in dry weight were observed in both leaves and branches between May/June and August; growth then slowed considerably and virtually ceased after October. Clear seasonal changes in 137 Cs activity concentrations were observed in both 2016 and 2017, regardless of tree species. Concentrations were higher in young leaves and branches during May and June, then decreased and changed relatively little from August to winter. Reduced 137 Cs activity concentrations in dead leaves of Q . serrata were observed only in December 2017 (approximately 15% lower than in October). This reduction may indicate reabsorption of 137 Cs in leaves prior to shedding. The changes in potassium concentrations were similar to those in 137 Cs in both years. Potassium concentrations were higher in young leaves than in mature leaf and branch samples collected later in the year. A reduction of about 50% in the potassium concentrations in dead leaves of Q . serrata was also observed in December. A positive relationship between 137 Cs and potassium concentrations in leaves and branches was observed in all species, except for planted Q . serrata . This relationship may indicate that 137 Cs moves in tree shoots with potassium. Leaf and branch weight correlated negatively with 137 Cs and potassium concentrations. Reduced concentrations may indicate dilution of these elements as a result of biomass increases over the growing season. Our results imply that irrespective of species, 137 Cs exhibits seasonal variations resulting from dilution; these variations correspond with trends in potassium, with higher levels in young organs and decreased levels in older organs. Highlights: 137 Cs and K levels were higher in young leaves and branches than in older ones. 137 Cs and K levels decreased and changed relatively little from August to winter. Reabsorption of 137 Cs in leaves prior to shedding was observed in deciduous tree. A positive correlation was observed between 137 Cs and K concentrations. The negative relationship between biomass and 137 Cs indicates a dilution effect.